The Resilience and Agricultural Household Livelihood Strategies of the 2018 Lombok Earthquake Victims at the Emergency Period in North Lombok Regency - Muhammad Nurjihadi (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2020)
A great earthquake was hitting Lombok in August 2018 that caused damage to home and livelihood sources of almost 100% of North Lombok Regency (KLU) population. This research is aimed to investigate the resilience capacity and livelihood strategies of displaced people (the earthquake victims) of KLU, especially the agricultural families during the post disaster emergency period. This research is using mix method between qualitative and quantitative approaches that explained descriptively. The qualitative data in this research was obtained using purposive area snowball sampling technique while the quantitative data was obtained through a comprehensive survey using Displacement Tracking Matrix (DTM) technique. Result of the research revealed that the earthquake caused the lost of jobs and livelihood sources of KLU’s people in all economic sectors, including agricultural sector. Social capital of the society was influencial as a main strategy of the victims to fulfil their daily needs and strengthen their social resilience in facing the damaging impact of the disaster. By exploiting their social capital, the society was able to fulfil their daily needs by managing all external aids, natural resources, and their remaining personal assets based on their common understanding, local wisdom, and social norms that exist in the society.